2014
DOI: 10.18352/ijc.416
|View full text |Cite
|
Sign up to set email alerts
|

Governing large-scale social-ecological systems: Lessons from five cases

Abstract: This paper compares lessons drawn from five case studies of large scale governance of common-pool resources: management of forests in Indonesia,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
84
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(87 citation statements)
references
References 48 publications
2
84
0
1
Order By: Relevance
“…The literature on design principle makes a strong call to the notion that configurations of design principles are necessary for success [1,25,32,47]. Baggio et al [47] analyzed the co-ocurrence of design principles by activity (fishery, irrigation and forestry) and the combinations of design principles leading to social and ecological success (sample of 69 cases).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature on design principle makes a strong call to the notion that configurations of design principles are necessary for success [1,25,32,47]. Baggio et al [47] analyzed the co-ocurrence of design principles by activity (fishery, irrigation and forestry) and the combinations of design principles leading to social and ecological success (sample of 69 cases).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the applicability of the theory to more complex situations has been questioned [24,26,27], and has become a field of active research in recent years [15,[28][29][30][31]. For example, Fleischman et al [32] analyzed the applicability of the institutional design principles (underlying principles that characterize robust institutions) 2 [1,2] in five large-scale governance systems, suggesting strong support to some principles and weak support to others; at large scales, other kinds of political dynamics, including the role of scientists and civil society organizations, appear to play key roles. This study aimed to analyze the governance of the Cassurubá RESEX, Bahia State, Brazil, through exploring key stakeholders' perceptions about its functioning and prospects, and examining the enabling conditions present and the difficulties faced by this new and ambitious governance system.…”
Section: Introductionmentioning
confidence: 99%
“…Challenges with some design principles at large scales also reflect the conclusions of Social-Ecological Systems Meta-Analysis Database (SESMAD) case studies , Fleischman et al 2014, Cox 2014. The SESMAD project seeks to determine if important variables, including the design principles, for small-scale systems can be effectively scaled up for large-scale governance systems (Cox et al 2010).…”
Section: Challenges To Scaling Up Design Principles For a Federal Resmentioning
confidence: 99%
“…The SESMAD case study of the International Convention for the Conservation of Atlantic Tuna also found that collective choice, rights to organize, and nested governance were either absent or unsuccessful on a large scale . However, the authors posit that other mechanisms available at a federal scale, such as political dynamics and civil society interactions, may help to mitigate against governance failures , Fleischman et al 2014. Although some design principles were less applicable on a large scale, the majority of these attributes were equally applicable for small-and large-scale systems, indicating that they can be useful to assist in making management recommendations.…”
Section: Challenges To Scaling Up Design Principles For a Federal Resmentioning
confidence: 99%
“…There is thus a need to understand better whether and how these ideas apply to large SESs (Fleischman et al 2014, Cox 2015. At the same time, it is urgent to move toward sustainable use of resources and management of common-pool resources (e.g., Poteete et al 2010).…”
Section: Introductionmentioning
confidence: 99%